PENGEMBANGAN BAHAN AJAR FIQIH HAID BERBASIS MODUL AJAR DI MADRASAH IBTIDAIYAH NURUL HASAN KADEMANGAN MALANG - Nihayatin Nimah; Evi Nurhalimah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to develop teaching materials on Fiqh related to menstruation in the form of teaching modules tailored to the needs and characteristics of students at Madrasah Ibtidaiyah (MI) Nurul Hasan Kademangan, Malang. The background of this study is the low level of understanding among female students regarding the concept of menstruation from a Fiqh perspective including legal aspects, etiquette, and purification procedures even though some of the students have already experienced menstruation. This study employed a Research and Development (R&D) approach using a modified Borg and Gall model, encompassing the stages of needs analysis, design, development, expert validation, limited pilot testing, and product revision. Data were collected through observation, interviews, questionnaires, and documentation, and were subsequently analyzed using descriptive qualitative and quantitative methods. The results of the study indicate that the developed teaching module possesses good levels of validity and practicality and is effective in enhancing students’ understanding of Islamic laws and etiquette regarding menstruation. This teaching module is expected to serve as an innovative and contextual learning resource that supports the development of religious character among female students in Madrasah Ibtidaiyah